Peningkatan Toleransi Rendaman Padi Lokal Rawa Lebak dengan Introgresi Gen Sub1 - ,, Gusmiatun; Suwignyo, Rujito A.; Wijaya, Andi; Hasmeda, Mery (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTOne of efforts to increase rice production at swamp area which is frequently flooded is the use of submergence tolerant rice varieties. The objectives of this research was to improve plant tolerance after submergence stress for 14 days in BC1F1 of crosses between local superior varieties and Sub1 gen donor (FR13A). The studies were carried out in two stages: 1) Crossing local superior varieties, i.e., Pegagan (Pgn), Siam (Sm), Payak Selimbuk (Pys), dan Pelita Rampak (Plr) to submergence tolerant variety FR13A; and 2) submergence tolerance evaluation of the progeny. The first study was conducted at green house of Graduate Study Sriwijaya University, Palembang. The second study was carried out at field experiment of Central Research and Development of Agricultural Biotechnology and Genetic Resources in Bogor. All studies were conducted from March 2011 until March 2013. The first study was the introgression of Sub1 gene into local genotypes Payak Selimbuk, Pegagan, Siam and Pelita Rampak from FR13A. The second study was evaluation of BC1F1 plant performance after submergence treatment for 14 days. The results showed that introgression of Sub1 gene into local varieties improved submergence tolerance as indicated by higher percentage of survived plants, lower decrease of plant dry weight, and lower decrease of grain weight per panicle compared to parents.Keywords: Sub1 gene, local swamp rice, submergence tolerant